Gastric Prolapse with Pseudocysts Following Laparoscopic Adjustable Gastric Banding - Glenn, Jason A. (Society of Laparoendoscopic Surgeons, 2011)
INTRODUCTION: Laparoscopic adjustable gastric banding (LAGB) is a reversible method of surgical gastric restriction. Following LAGB, the adverse event most commonly necessitating subsequent reoperation is prolapse of the gastric corpus or fundus above the band. A review of the medical literature reveals no reports of nonpancreatic pseudocysts being associated with this adverse event. Nonpancreatic pseudocysts, encountered during revisional bariatric surgery should be considered a cause of irreducible gastric prolapse. CASE REPORT: We report the case of a 41-year-old Caucasian female who underwent laparoscopic surgery to revise an adjustable gastric band and to repair an anterior gastric prolapse. Intraoperatively, 2 pseudocysts were found on the gastric fundus above the band in association with the gastric prolapse. The pseudocysts were resected, the gastric prolapse was reduced, and the band was left in place. The patient recovered uneventfully. CONCLUSION: Nonpancreatic pseudocysts may be associated with gastric prolapse in patients who have undergone LAGB. These pseudocysts can often be excised laparoscopically without violating the gastric lumen. This atypical presentation of gastric prolapse may pose a diagnostic and therapeutic challenge as these patients may present to an outpatient clinic or emergency room with nonspecific symptoms.